A Study on Scholarly Productivity and Leadership Profiles of LIS Experts in India from Lib-Vahini Database - Gunaseelan, S.; Abbas, L. Mohammad; Rajkumar, N.; Shanmuganathi, A. (Journal of Data Science, Informetrics, and Citation Studies, 2026)
This study examines the professional landscape of LIS experts in India using data from the LIB-VAHINI (Virtual Access Hub for Innovation, Networking, and Integration) platform, which includes 3,217 experts across more than 100 organizations. Analysis focuses on organization-wise and state-wise distribution, designation profiles, scholarly productivity, alt metric indicators, and prominent expert contributions. Results indicate that colleges and state public universities account for the majority of experts, with Tamil Nadu, Maharashtra, and Karnataka showing the highest state-wise representation. Librarians constitute the largest professional group, followed by assistant librarians and assistant professors. A total of 39,702 publications, alongside high social media engagement and Mendeley readership, reflect strong scholarly output and digital presence. Leading institutions and distinguished experts are identified for their substantial contributions to the field. The findings offer insights for policymakers, academic administrators, and LIS professionals to enhance networking, skill development, research collaboration, and professional recognition in India.
Keywords: Academic Collaboration and Scholarly Productivity; LIB-VAHINI; LIS experts; Professional Networking